Potassium-Competitive Acid Blocker (P-CAB) Generasi Baru: Studi Farmakologi dan Klinis Vonoprazan Fumarate: A New Generation of Potassium-Competitive Acid Blockers (P-CAB): Pharmacological and Clinical Studies of Vonoprazan Fumarate - Ilahi, Ade Rezki; Febrina, Ellin (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
The aim of this study was to determine the pharmacological profile, clinical effectiveness, and safety of Vocinti (vonoprazan fumarate) as a P-CAB class gastric acid secretion inhibitor therapy. The method used was a literature review with a qualitative-descriptive approach. Information was collected, manually sorted and critically reviewed to ensure its validity and relevance, in order to produce a comprehensive picture of the pharmacological aspects, clinical effectiveness, and safety of Vocinti use. Based on the available literature review, Vocinti (vonoprazan fumarate) as a P-CAB class gastric acid secretion inhibitor therapy shows a superior pharmacological profile compared to conventional PPIs. Vonoprazan works through reversible competitive inhibition of the H+/K+-ATPase enzyme, resulting in faster, stronger, and more consistent acid suppression, with a longer duration of action and independence from acid activation. Thus, vonoprazan is worthy of consideration as an alternative primary therapy for gastric acid disorders, especially in refractory patients or those requiring long-term therapy. Keywords: P-CAB, Vonoprazan Fumarate Clinical, Pharmacological Studies, Vocinti